Croco - López, Azul, 1991- (Tapioca Stories, 2025)
"In a vibrant tropical jungle, Croco the Crocodile has fallen into a hole and can't climb out. Different animals come along to try to help him, but in the end, he must find his own way out. This charming picture book for early readers teaches us about resilience and the importance of helping others, no matter the obstacles in our way. Croco, the protagonist, tries to follow the advice of his friends to escape his predicament, only to realize the solution was within him all along. The story builds tension as Croco remains trapped, culminating in a satisfying ending that restores harmony and marks his growth. A simple story about an everyday problem, this book draws readers in with its steadily building suspense. Set in a lush tropical jungle full of vibrantly colored animals, the book's illustrations create striking visual contrasts across different scenes. Croco, positioned at the bottom of the page, tries various strategies to climb out of the hole, while the animals above him attempt to assist him. The carefully composed artwork features expressive brushstrokes and meticulously arranged characters, establishing a dynamic visual rhythm between the two planes--the world above, where the animals try to help, and the world below, where the bright red protagonist struggles to escape his accidental trap. Young readers will root for Croco as he navigates his challenges, making this a heartwarming tale of perseverance and friendship"--